Pastoral Konseling Terhadap Jemaat yang Menderita Hipertensi Akibat Pola Hidup yang Tidak Sehat - Rinaldi Dharmawan; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
Unhealthy life patterns due to the habit of consuming foods that are high in fat content and lazy habits in exercising often cause problems. One of the problems that often arises from this is hypertension which according to statistical data is a disease that is classified as a silent killer if not treated immediately. Even young age is not a guarantee that someone will not suffer from hypertension. Lack of awareness that the body should be looked after and presented as a holy sacrifice before God is a trigger for an unhealthy lifestyle. Hypertension is a disease that is often found among the congregation in a church, and the church as God's representative must be able to provide pastoral counseling assistance for congregations who suffer from this disease and provide solutions for the congregation and their families.